Role of vasoactive substances in the segmentary vasomotor response following spinal cord stimulation: an experimental study (1990)
It is presumed today that spinal cord stimulation induces local delivery of vasoactive substances, such as prostacyclins, histamine, substance P, and vasoactive neuropeptides, in the perivascular environment and the vascular wall to mediate the segmental vasodilator response. To investigate this mechanism, 9 dogs were subjected to low thoracic spinal cord stimulation. Venous and arterial blood samples from the paresthesic area in the lower limbs were obtained before and 120 min after stimulation to measure changes in the plasma concentration of vasoactive intestinal peptide, substance P, and histamine. The results were compared with those obtained from vessels of the upper limbs. Blood flow changes following stimulation were recorded by electromagnetic flowmeters. Local arterial vasoactive intestinal peptide showed a mean increase of 33% after 60 min of stimulation. Changes concerning substance P were inconclusive. Local arterial and venous histamine concentrations increased 26 and 29%, respectively, after 60 min of stimulation.